Struktur Gerak Silek Galombang Pada Sanggar Tunas Harapan Nagari Aua Kuniang Kabupaten Pasaman Barat - Retno Kartika; Yuliasma Yuliasma (SENDRATASIK UNP, 2021)
This research aims to reveal and describe the structure of Gerak Silek Gelombang Sanggar Tunas Harapan Nagari Aua Kuniang Pasaman Barat. This type of research is qualitative research using content analysis methods. The data type uses primary data and secondary data. The main instrument in this study was the researcher himself and assisted with supporting instruments such as stationery, camera and flash drive. Data collection techniques are done by means of library studies, observations, interviews, documentation. The steps of analyzing data are collecting data, describing data and concluding data. The results showed that the structure of dance motion galombang silek is analyzed with three stages consisting of the system of relationships between basic elements, grammatical hierarchical relationships and syntagmatic and paradigmatic relationship systems. The relationship between the basic elements of silek galombang dance, has a basic element that relates to attitudes and motions on the head, body, hands and feet that produce motifs that overlap and alternate attitudes. Grammatical hierarchical relationship in silek galombang dance consists of 47 motifs with 27 forms of basic motifs, phrases as many as 23 phrases, sentences as many as 9 sentences and 1 cluster. In this dance there is a syntagmatic relationship system in which this dance can not be reversed because every motion is bound and overlapping and there are also paradigmatic relationships on some motifs where this dance can be reversed.